Clinical and echographic signs of acute kidney injury in premature babies born with very low and extremely low body weight - A. K. Mironova; I. M. Osmanov; I. N. Zakharova; M. I. Pykov; E. L. Tumanova; S. L. Morozov; T. I. Vokuyeva (Медицинский совет, 2021)
Introduction. One of the urgent issues in the first stage of nursing premature infants is acute kidney injury. The incidence of neonatal acute kidney injury in developing countries is 3.9/1000 live births, with 34.5/1000 among neonatal intensive care patients.The aim of the study was to establish echographic signs of acute kidney injury in deeply premature infants in the neonatal period.Materials and methods. 24 children with clinical and laboratory signs of acute kidney injury “AKI+” and 76 children without signs of acute kidney injury “AKI-“. All the children included in the study were born with a body weight of less than 1500 g and a gestation period of less than 32 weeks and were in the neonatal intensive care unit. To clarify the nature of the detected changes, a scientific analysis of the results of pathoanatomic studies of 55 deceased preterm infants was carried out.Results. In all children from the “AKI+” group, there was a pronounced diffuse-uneven increase in the echogenicity of the parenchyma, there was a depletion of the vascular pattern in the subcapsular zone and/or in the cortical layer of the parenchyma, in 25% of patients on the 5th-15th day of life, anechogenic formations without signs of blood flow, with a diameter of 1-3 mm in the cortical layer were noted. The changes had a bilateral nature of the lesion, with further observation they were gradually reduced and by 3 ± 2 months of life they were not determined during ultrasound of the kidneys.Discussion. Acute kidney injury is an urgent problem of preterm infants born with very low and extremely low body weight. The article presents the results of ultrasound examination of the kidneys in comparison with clinical and laboratory indicators and the results of pathomorphological studies. As a result of the study, the most characteristic ultrasound signs of acute kidney injury were identified, which are an uneven diffuse increase in the echogenicity of the renal parenchyma, small anechoic avascular inclusions (cysts) of the parenchyma, depletion of renal blood flow.Conclusions. Renal ultrasonography is an informative method, but echographic changes may be labile depending on the clinical course of the disease, and the absence of anechogenic masses in the parenchyma may be due to technical limitations of the ultrasonography method. It requires further monitoring and continued vigilance of the pediatrician and pediatric nephrologist.